Epistemologia, estetica e pluralismo - Di Prospero, Alfonso (Scenari, 2024)
My approach is within an empiricistic and inductivistic framework, where induction is seen as a non-monotonic inference. Thus I interpret the cognitive meaning of art in terms that are – consistently with a non-monotonic epistemology – relative to the field of experience and information that is available to a specific subject. Moving from these premises, Shusterman’s idea that popular music is properly art is defended. Noë’s claim that popular music is not art is criticized also because it is not consistent with the entailments deriving from an embodied mind theory when we accept a non-monotonic epistemology.